Highly Efficient Bifunctional Dielectric Metasurfaces at Visible Wavelength: Beam Focusing and Anomalous Refraction in High-Order Modes - Xu, Zhenyu; Li, Zhiwei; Tian, Yanqing; Wei, Yunbing; Wu, Fei (Frontiers in Physics, 2020)
Metasurface is an artificially arranged sub-wavelength micro-structure array. Each structure can be regarded as an unit cell controlled by electromagnetic wave. Recently, bifunctional metasurfaces have aroused increasing interest and become excellent candidates for device miniaturization and integration. In this paper, we propose a highly efficient bifunctional metasurface, composed of silicon nanopillars, enabling anomalous beam deflection and focusing at visible wavelength. Based on the designed metasurface, the other two metasurfaces are presented successfully, demonstrating high-order anomalous beam deflection and focusing. This work will establish a positive prospect for the development of high-performance bifunctional metasurface.